Complexo portuário do Maranhão e desenvolvimento regional - CASSIA, Gabriel Fernando Mateucci (2023)
This dissertation investigates port development in light of the theory of economic complexity, with a focus on the Itaqui Port Complex located in the state of Maranhão, Brazil. The study analyzes the international port system, with emphasis on countries such as China, Singapore, South Korea, and the Netherlands, aiming to understand economic complexity and maritime transport connectivity in these contexts. The study establishes the importance of port development for national economies and the need to understand the factors influencing this process. It is observed that an efficient port system capable of generating positive externalities requires a country that produces and exports highly complex products, necessitating ports with infrastructure for handling high-value cargo. Countries that have experienced significant port development have implemented long-term industrialization policies, with active state participation and investments in industrial sectors, protecting domestic industries and directing resources towards education, research, and innovation. In the Brazilian case, the concentration of industrial development in the Southeast region and the abandonment of industrialization policies since the 1980s have resulted in the primarization of the economy, with the export of raw agricultural and mineral commodities. This has impacted the port sector, which has become infrastructure for the shipment of these commodities rather than focusing on higher-value cargo. In the Itaqui Port Complex, despite the significant cargo movement, few positive externalities for the local territory and population are evident. The goods handled have low complexity, limiting productive connections and co-exportation. Finally, it is observed that local economic development, through existing port infrastructure, requires a national development policy capable of increasing the complexity of products handled by Brazilian ports and generating value-added through productive chains. However, even in the absence of a consistent national policy, the theory of complexity can serve as a reference for the creation of local development policies, aiming to develop more complex and interconnected productive chains linked to the local productive fabric, generating positive externalities.